New Multicast Routing Protocols for Mobile Adhoc networks (International Journal of Engineering and Computer Science, 2017)
The majority of applications are in areas where quick deployment and dynamic reconfiguration are necessary and a wire network is not available for that areas. These include military battlefields, emergency search and rescue sites, classrooms, and conventions where participants share information dynamically using their wireless devices. Well established routing protocols do exist to offer efficient multicasting service in conventional wired networks. These protocols, having been designed for fixed networks, may fails to keep up with node movements and frequent topology changes in a MANET. Therefore, adapting existing wired multicast protocols as such to a MANET, which completely lacks infrastructure, appear less promising. Providing efficient multicasting over MANET faces many challenges, includes scalability, quality of service, reliable service, security, Address configuration, Applications for multicast over MANET. The existing multicast routing protocol do not addresses these issues effectively over Mobile Adhoc Networks (MANET).